Eksplorasi Pengalaman Siswa dalam Menghadapi Bullying di SMP SWT Utama Medan - Aprila, Gusti; Juliani, Duwi; Pulungan, Syarah Nabila (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This study aims to explore students’ experiences in dealing with bullying at SMP SWT Utama Medan. Bullying is a serious issue that can negatively affect students’ mental health, emotional well-being, and social development. Using a qualitative approach and case study method, data were collected through in-depth interviews with students who have experienced bullying, as well as through school environment observations. The findings reveal that students encountered various forms of bullying, including verbal, physical, and social abuse. Their responses varied, ranging from withdrawal and seeking support from peers or teachers to direct confrontation. Factors such as family support, teacher involvement, and school policies significantly influenced students’ ability to cope with bullying. These findings are expected to provide input for schools to create a safer and more supportive environment, as well as to raise awareness of the importance of early bullying prevention.